An Analysis of the Factors Influencing Energy Consumption Based on the STIRPAT Model: A Case Study of the Western Regions of China - Yi Zhu; Chao Feng; Xieqihua Liu; Tao Zhang; Xi Wang (Energies)
Understanding the factors influencing energy consumption is crucial for sustainable development. This study quantitatively analyzes the factors influencing energy consumption in China’s western regions from 2000 to 2022, employing the STIRPAT model, cointegration analysis, and ridge regression. Focusing on population size, economic development, industrial structure, urbanization, and technological progress, the results reveal significant heterogeneity in their impacts. Urbanization exhibits the strongest positive effect, with a 1% increase leading to a 0.483% rise in energy consumption, followed by economic development and industrial structure. Population growth has a modest positive influence, while technological progress demonstrates a mitigating effect, reducing energy demand. The findings underscore the critical role of urbanization and industrial restructuring in shaping energy consumption patterns. Policy recommendations emphasize optimizing urban layouts, accelerating industrial upgrades, and promoting technological innovation to achieve sustainable energy development in the region. These insights provide a foundation for targeted policies to balance economic growth with energy efficiency in Western China.